1994
DOI: 10.1093/cvr/28.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a nitric oxide synthase inhibitor in humans with septic shock

Abstract: Low doses of L-NMMA cause a widespread increase in vascular tone and raise blood pressure in patients with septic shock. Overproduction of nitric oxide appears to be an important mechanism in septic shock in patients, and inhibition of nitric oxide synthesis might provide a novel therapeutic approach to this condition. However, L-NMMA produced a fall in cardiac output and it is possible that this would worsen tissue perfusion. Larger studies examining the effects of L-NMMA on mortality and morbidity are now re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
188
1
5

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(200 citation statements)
references
References 0 publications
6
188
1
5
Order By: Relevance
“…We demonstrate here, however, that infusion of L-NMMA, at doses which attenuated the fall in MABP caused by endotoxaemia in the pig, did not exacerbate the endotoxin-induced fall in platelet or polymorphonuclear cell counts. Similarly, in patients with septic shock, L-NMMA enhances the peripheral vascular resistence without exacerbating the thrombocytopenia or neutropenia associated with sepsis (Petros et al, 1994).…”
Section: Mortalitymentioning
confidence: 96%
“…We demonstrate here, however, that infusion of L-NMMA, at doses which attenuated the fall in MABP caused by endotoxaemia in the pig, did not exacerbate the endotoxin-induced fall in platelet or polymorphonuclear cell counts. Similarly, in patients with septic shock, L-NMMA enhances the peripheral vascular resistence without exacerbating the thrombocytopenia or neutropenia associated with sepsis (Petros et al, 1994).…”
Section: Mortalitymentioning
confidence: 96%
“…Several small and uncontrolled studies demonstrated that short-term nonselective NOS inhibition increased both BP and systemic vascular resistance and decreased cardiac output in patients with septic shock (65)(66)(67). Beneficial effects on renal function were, however, not reported.…”
Section: Inhibition Of Nitric Oxide Synthasementioning
confidence: 99%
“…Similarly, in vivo studies have shown that the diminished pressor response to vasoconstrictors in endotoxic shock is reversed by NOS inhibitors (Gray et al, 1991;Szabo et al, 1993). Moreover, L-NMMA can alleviate the severe hypotension associated with endotoxaemia, both in animal models (Kilbourn et al, 1990;Thiemermann & Vane, 1990) and in humans (Lin et al, 1994;Petros et al, 1994). Third, and most convincingly, transgenic mice possessing a null mutation for the iNOS gene do not become hypotensive, nor do they succumb as readily as wild-type animals to treatment with bacterial endotoxin (MacMicking et al, 1995;Wei et al, 1995).…”
Section: Introductionmentioning
confidence: 98%